Engineering construction contract and the obligations of its parties - Alaa-Eldin Mohamed Moussa Elgizuli, (International Journal of Law Research and Studies, 2026)
The study addressed the concept of engineering construction contracts and their characteristics and the obligations of their parties, and the importance of this research is through the importance of engineering construction contracts, and the research followed the analytical inductive approach, and the research concluded many results, including that the structural engineer is committed to provide advice and advice During the various stages of construction processes, the performance of the construction engineer is characterized by a mental and mental nature and performs work independently of the employer with whom he entered a contract and from the executor and one of the most important recommendations is the need to set conditions for the practice of the profession of structural engineering and to be one of the items of punishment Engineering constructions explain that the commitment to information and insight falls on each professional and covers both the pre- and post-contract stages.
Keywords: Contract; Construction; Geometric